2019
DOI: 10.1182/bloodadvances.2018028514
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid translocation gene CBFA2T3 directs a relapse gene program and determines patient-specific outcomes in AML

Abstract: CBFA2T3 is a master transcriptional coregulator in hematopoiesis. In this study, we report novel functions of CBFA2T3 in acute myeloid leukemia (AML) relapse. CBFA2T3 regulates cell-fate genes to establish gene expression signatures associated with leukemia stem cell (LSC) transformation and relapse. Gene set enrichment analysis showed that CBFA2T3 expression marks LSC signatures in primary AML samples. Analysis of paired primary and relapsed samples showed that acquisition of LSC gene signatures involves cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…We demonstrated that one mechanism by which CBFA2T3 and RUNX1 promote leukemogenesis or maintain leukemia is by controlling cell proliferation. Our results are concordant with data from Steinauer et al showing that downregulation of CBFA2T3 arrests G1/S cell cycle progression and attenuates in vitro and in vivo proliferation of acute myeloid leukemia cells [50].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We demonstrated that one mechanism by which CBFA2T3 and RUNX1 promote leukemogenesis or maintain leukemia is by controlling cell proliferation. Our results are concordant with data from Steinauer et al showing that downregulation of CBFA2T3 arrests G1/S cell cycle progression and attenuates in vitro and in vivo proliferation of acute myeloid leukemia cells [50].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are concordant with data from Steinauer et al . showing that downregulation of CBFA2T3 arrests G1/S cell cycle progression and attenuates in vitro and in vivo proliferation of acute myeloid leukemia cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a nuclear co-repressor, ETO2 interacts with DNA-binding transcription factors and recruits a range of corepressors to inhibit downstream gene expression, therefore, it plays a critical role in the regulation of the cell cycle, self-renewal capacity, and differentiation of hematopoietic progenitor cells [7]. ETO2 indirectly promoted leukemia stem cells transformation and guided a relapse gene program which induced dismal clinical outcomes in AML [8]. To our knowledge, ve ETO2 fusion genes have been reported in hematological malignancies up to date, including inv(16)(p13.3q24.3)/ETO2-GLIS2 [2,9],t(1;16) (p31;q24)/NFIA-ETO2 [10] and t(16;21)(q22;q24)/RUNX1-ETO2 [11] in AML, t(9;16)(p13;q24)/PAX5-ETO2 [12] in ALL and t(14;16)(q32;q24)/IGH-ETO2 [13] in lymphoma.…”
Section: Case Reportmentioning
confidence: 99%
“…Underscoring its important role in hematopoietic transcriptional regulation, CBFA2T3 is frequently involved in leukemogenic translocations producing CBFA2T3 fusion proteins, including RUNX1-CBFA2T3 in therapyrelated AML (14) and CBFA2T3-GLIS2 in pediatric AMLs (15). WT CBFA2T3 plays important roles in both normal and malignant hematopoiesis, where it inhibits terminal erythromegakaryocytic differentiation (16), maintains stemness of long-term hematopoietic stem cells (HSCs) (17), and promotes the expansion of leukemia stem cells (LSCs) and AML relapse (18). Intriguingly, CBFA2T3 knockout in murine HSPCs promotes differentiation along the granulo-monocytic lineage at the expense of erythro-megakaryocytic development, phenocopying the effect of ATRA treatment (19,20).…”
mentioning
confidence: 99%